Sistem Informasi Revervasi Pelatihan dan Simulasi Berbasis Web pada Damkar Kota Surakarta - Yeremia Dhimas Abiyoso; Nibras Fa'id Muhammad; Sri Sumarlinda (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2025)
The Surakarta City Fire Department has a major responsibility in firefighting and rescue operations. Currently, the process of managing training and simulation requests is still carried out manually, often through official correspondence. This manual approach leads to various issues such as disorganized data management, the potential for overlapping or missed schedules, errors in recording dates, insufficient communication between officers, and difficulties in managing training history and evaluation results.This study aims to design and develop a web-based information system for managing training and simulation requests to address these challenges. The system is expected to simplify the management of reservation requests, minimize scheduling errors, and improve transparency and accountability. The system development method used is Rapid Application Development (RAD), which includes the following stages: requirements planning, user design, construction, and cutover. Data were collected through direct observation at the Surakarta City Fire Department, interviews with the Head of the Department and the Department Secretary, and literature studies. The system will be developed using the PHP programming language and the Laravel framework, with a MySQL database. With this system, the Surakarta City Fire Department is expected to improve the efficiency and effectiveness of training and simulation management at the department.